5-aminosalicylic acid improves lipid profile in mice fed a high-fat cholesterol diet through its dual effects on intestinal PPARγ and PPARα. - Zheng Wang; Debby Koonen; Marten Hofker; Zhijun Bao (PLoS ONE, 2018)
Obesity is associated with a series of metabolic complications, including dyslipidemia and insulin resistance (IR) that lack effective therapies. In recent years, intestinal inflammation has been suggested to contribute to obesity related metabolic syndrome and targeting gut inflammation with 5-ASA improves diet induced IR, however, its role in dyslipidemia is unknown and has never been explored. In the present study, we reported for the first time that administration of 5-ASA for 12 weeks significantly improved lipid profile by repressing plasma triglycerides and free cholesterol levels in mice fed high-fat cholesterol diet (HFC). In addition, liver lipids were significantly reduced by 5-ASA treatment in HFC-fed mice. Mechanistically, anti-inflammatory genes peroxisome proliferator-activated receptor-γ (Pparγ) and M2 marker, such as Mrc1 and Ym1, were remarkably upregulated, while pro-inflammation gene monocyte chemoattractant protein-1 (Mcp-1) were downregulated in small intestine of mice treated by 5-ASA. Further, 5-ASA improved gastrointestinal barrier by increasing the expression of the tight junction marker ZO-1. 5-ASA also enhanced cholesterol translocation by elevating genes expression of Npc1l1 and Abcg5/8. Moreover, mice fed HFC 5-ASA expressed increased Pparα in small intestinal and its target genes function in lipid oxidation and hydrolysis were remarkable elevated. Taken together, we reported a novel role of 5-ASA which may serve as a therapy target intestinal inflammation induced dyslipidemia.